Community-based screening for cardiovascular risk using a novel mHealth tool in rural Kenya. (2018) - Mannik, Jennifer R.; Figol, Andrea; Churchill, Venessa; Aw, James; Francis, Stacy; Karino, Ezekiel; Chesire, Julius Kibet; Opot, Danet; Ochieng, Benard; Hawkes, Michael T.
No abstract available